Hyper-IgE syndrome: A rare case report - Lee Smith, PhD; Ahmed Rafei, MD; Susanna Caminada, MD; Salma Barakat, MD; Sami Medani Abd Elwahab, MD; Damiano Pizzol, PhD; Abdelmounem Eltayeb Abdo, PhD (Journal of Allergy and Clinical Immunology: Global)
Hyper-IgE syndrome (HIES) is a rare and sporadic primary immunodeficiency usually characterized by atopic dermatitis, recurrent skin staphylococcal infections, recurrent pulmonary infections, and elevated IgE levels. Due to the rarity of the syndrome and its nonspecific and wide presentation, the diagnosis is difficult and arises with other diagnoses including other types of primitive chronic granulomatous disease or acquired immunodeficiency, severe atopic dermatitis, or cystic fibrosis or chronic respiratory infection as tuberculosis. To date, there is no gold standard management and treatments aim to relieve symptoms and avoid complications. We report on a 30-year-old female with a long-time misdiagnosed HIES.